Implementation and Impact of Augmented Reality in Education for Sustainable Development (ESD) for Science Learning: A Systematic Literature Review - Inanda Aulia Rizqillah; Mita Anggaryani; Mohammad Budiyanto; Muhammad Satriawan (IJIS Edu : Indonesian Journal of Integrated Science Education, 2026)
Augmented Reality (AR) has gained increasing attention in science education due to its potential to support interactive and contextual learning experiences aligned with the goals of Education for Sustainable Development (ESD). This systematic literature review aims to examine the implementation of AR in science learning, the learning outcomes achieved through AR-based interventions, and the extent to which AR supports sustainability-related competencies. A systematic search and selection process resulted in 35 relevant studies, which were analyzed using thematic synthesis. The findings indicate that AR is predominantly implemented through mobile-based and marker-based technologies within learner-centered and inquiry-oriented learning environments. AR-supported science learning is reported to enhance cognitive and affective learning outcomes, including conceptual understanding, motivation, and engagement. From an ESD perspective, AR shows potential in fostering sustainability-related competencies, particularly environmental awareness, systems thinking, and responsible attitudes. However, the review reveals that the integration of AR with explicit ESD competency frameworks and pedagogically grounded instructional designs remains limited. This study highlights the need for future research to strengthen the alignment between AR technologies, instructional models, and sustainability-oriented learning objectives to maximize the contribution of AR to science education for sustainable development.